TOLERANSI BERAGAMA DALAM PARADIGMA TAFSIR MAQASIDI - Muhammad Halif Asyroful Bahana (AL-BAYAN INSTITUTE, 2022)
Maqāşidi interpretation plays a crucial role in connecting the two main streams, namely literalist (textual) thinking and contextual interpretation. In maqasidi interpretation, various values are contained, including: the value of justice, the value of humanity, the value of equality, the value of moderation, and the value of freedom or responsibility. The stigma that Islam is a religion of violence is a labeling of recent terrorist acts. This can lead to the Qur'an as a source of ideology. Whereas Islam and the Qur'an both aim to uphold harmony and spread love. This article discusses the concept of tolerance from the perspective of Tahir Ibn Ashur's maqasidi tafsir. This research uses the literature review method, in Ibn Assyria's view there are four principles of tolerance that are initiated, including al-Fitrah, al-Samahah, al-Musawah, and al-hurriyyah.